ROLE OF ARTIFICIAL INTELLIGENCE TECHNOLOGIES ON CUSTOMER BEHAVIOUR: EVIDENCE FROM CONSUMER GOODS COMPANIES IN SUB-SAHARAN AFRICA (Journal of the Management Sciences, 2025)
Advances in technology and the potential for artificial intelligence (AI) in customer behaviour are on the rise, and the possibilities are limitless. The tracking of customer behaviour has become increasingly complex due to the evolving marketing environment. This study emphasises the significance of artificial intelligence in enhancing customer behaviour and investigates the impact of artificial intelligence on consumer behaviour within selected consumer goods firms listed in Nigeria, the most populous nation and one of the largest economies in Africa. The study employed a cross-sectional survey methodology, identifying and assessing 20 consumer product firms based on capitalization criteria and consistent dividend disbursements. Seven companies were selected from this group for additional examination. The sample size of 378 was established with the Research Advisor Table, with a confidence level of 95% and a margin of error of 5%. To mitigate the problem of non-response, suitable actions were implemented, resulting in the incorporation of an extra 113 respondents, constituting 30% of the initial sample. The modification yielded a final sample size of 491. A total of 480 copies of the questionnaire were filled and returned for analysis, with a response rate of 97.76%. The idea was evaluated by regression analysis. This chapter indicates that artificial intelligence (AI) functions as both a technological resource and a strategic asset for understanding customer behaviour (β = 0.503, t = 10.251, p < 0.05). This indicates that artificial intelligence is a crucial determinant of consumer behaviour. The research indicates that organisations ought to utilise artificial intelligence (AI) solutions and technologies to enhance operational efficiency. By implementing AI, firms can optimise processes, save costs, and improve their adaptability to market volatility and customer demands.
Keywords: Business intelligence, Business performance, Consumer goods, Customer retention, Nigeria